Visual outcome of various dose of glucocorticoids treatment in nonarteritic anterior ischemic optic neuropathy– a retrospective analysis - Fang-Fang Zhao; Yun Chen; Tai-Ping Li; Yun Wang; Hong-Jie Lin; Jian-Feng Yang; Lan Chen; Shao-Ying Tan; Jia-Jian Liang; Ling-Ping Cen (BMC Ophthalmology, 2024)
Abstract Background and purpose The objective of this investigation was to assess the therapeutic efficacy of distinct glucocorticoid therapy dosages in the management of acute nonarteritic anterior ischemic optic neuropathy (NAION). Materials and methods This retrospective, unmasked, and non-randomized study included a total of 85 patients. The patients were categorized into four groups: Group 1 (control) consisted of 15 patients who did not receive glucocorticoids, Group 2 included 16 patients administered with oral prednisone at a dosage of 1 mg/kg/d for 14 days, Group 3 comprised 30 patients who received 250 units of methylprednisolone once daily for 3 days, followed by oral prednisone at a dosage of 1 mg/kg/d for 11 days, and Group 4 encompassed 24 patients who received 500 units of methylprednisolone once daily for 3 days, followed by oral prednisone at a dosage of 1 mg/kg/d for 11 days. The best-corrected visual acuity (BCVA) was assessed at baseline and the final follow-up (> 7 days post-treatment). The changes in visual acuity between baseline and the 7–14 day follow-up, as well as between baseline and the concluding appraisal, were employed as metrics for assessing the extent of visual enhancement. Results No significant differences were noted in the final visual outcomes or in the changes between final visual acuity and baseline across the four groups. In Group 1 (control), the best-corrected visual acuity (BCVA) remained unchanged during final follow-ups compared to baseline. Conversely, the intervention groups exhibited statistically significant enhancements in BCVA during final follow-up (p = 0.012, p = 0.03, and p = 0.009 for Group 2, Group 3, and Group 4, respectively) when compared to baseline. During the 7–14 day follow-up, there was a significant difference in the changes between baseline BCVA and follow-up BCVA across the groups (p = 0.035). Go a step further by Bonferroni correction for multiple comparisons, group 4 showed a greater change in vision compared with group1 (p = 0.045). Conclusion Our study on acute nonarteritic anterior ischemic optic neuropathy (NAION) showed no significant final visual outcome differences. Nevertheless, Groups 2, 3, and 4 demonstrated improved best-corrected visual acuity (BCVA) during the final follow-up. Notably, a 500-unit dose of methylprednisolone resulted in short-term BCVA enhancement. This suggests potential consideration of 500 units of methylprednisolone for short-term NAION vision improvement, despite its limited long-term impact.